Hemophilia A with Factor VIII Inhibitor in a Geriatric Patient: A Case Report - Pande Putu Rangga Raditya; Rikky Dwiyanto Sulistyo; Pendy Wastu Haribowo; Sylvi Diahningrum; Ryski Meirina Wiendanita; Paulina Yessica Pramadita M; Made Bayu Sanjaya Sanjaya (JURNAL KESEHATAN, SAINS, DAN TEKNOLOGI (JAKASAKTI), 2026)
Hemophilia A with Factor VIII Inhibitor in a Geriatric Patient: A Case Report. Hemophilia is an inherited bleeding disorder caused by a deficiency or abnormality of coagulation proteins. Its clinical manifestations are diverse, ranging from hemarthrosis, muscle hematomas, and mucosal bleeding to life‑threatening events such as intracranial hemorrhage. This article presents a case of a 60‑year‑old woman who developed a massive hematoma in the posterior femoral region, associated with factor VIII deficiency and the presence of factor VIII inhibitors. The discussion highlights the diagnostic approach, supportive laboratory investigations, pathophysiological aspects, and management strategies for hemophilia A in elderly patients complicated by hematoma.